1998
DOI: 10.1002/hep.510280131
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of immune responses to hepatitis C virus envelope E2 protein following injection of plasmid DNA using single or combined delivery routes

Abstract: Hepatitis C virus (HCV) has been identified as the principal agent of parenterally transmitted non-A, non-B hepatitis. 1,2 The distribution of HCV is worldwide with a prevalence estimated to range between 0.4% to 2% in the blood donor population. 3 More than 70% of infected patients develop chronic hepatitis with a risk of progression to cirrhosis and hepatocellular carcinoma. 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…The following boundaries were used: for the core protein, amino acids (aa) 1 to 191 (pCMVC2) (41); for E1, aa 134 to 328 (pCIE1t); for E2, aa 340 to 674 (pCIE2t); and for NS3, aa 1027 to 1657 (pCINS3) (3). The assessment of antigen production was performed as described previously (16,17,41). The constructs were used for the immunization of mice and elicited strong humoral as well as cellular immune responses (3, 41; G. Inchauspé, unpublished data).…”
Section: Animalsmentioning
confidence: 99%
“…The following boundaries were used: for the core protein, amino acids (aa) 1 to 191 (pCMVC2) (41); for E1, aa 134 to 328 (pCIE1t); for E2, aa 340 to 674 (pCIE2t); and for NS3, aa 1027 to 1657 (pCINS3) (3). The assessment of antigen production was performed as described previously (16,17,41). The constructs were used for the immunization of mice and elicited strong humoral as well as cellular immune responses (3, 41; G. Inchauspé, unpublished data).…”
Section: Animalsmentioning
confidence: 99%
“…This suggests that Ab responses could be an important protective correlate for protection against HCV infection. Previously, DNA vaccines expressing HCV core, E1, and E2 proteins have been shown to induce Ag-specific Ab and Th cell proliferative responses, as well as CTL in animals (Lagging et al, 1995;Major et al, 1995;Encke et al, 1998;Fournillier et al, 1998). Moreover, gene gun delivery of DNA vaccine containing both a codon-optimized synthetic HCV NS3/4A sequence and Semliki forest virus replicon resulted in an improved immunogenicity as evidenced by higher levels of NS3-specific antibodies (Frelin et al, 2004).…”
Section: Hepatitis Virusmentioning
confidence: 99%
“…Since E1 has been shown to be a poor immunogen in all studies reported so far [42,43], most of the gathered data are specific to E2-derived vaccines. Original studies have exploited different fusion contexts of the E2 protein in order to try and optimize its immunogenicity either by optimizing its capacity to be secreted or by favoring its expression on the cell surface.…”
Section: Induction Of E1-and E2-specific Immune Responsesmentioning
confidence: 99%